Efficacy of esketamine on perioperative anxiety in patients receiving anesthesia: a systematic review and meta-analysis of RCTs - Shi, Shang; Wang, Feng; Luo, Jieqiong; Yang, Fangzhou; Zou, Xiaohua (Frontiers in Psychiatry, 2026)
ObjectiveThis study aimed to assess the impact of esketamine on perioperative anxiety, including its frequency, intensity, and score variations, across different surgical procedures by analyzing data from randomized controlled trials (RCTs).MethodsA comprehensive literature search was performed across PubMed, Embase, the Cochrane Library, and Web of Science to identify relevant RCTs evaluating esketamine. Statistical analyses were conducted using Review Manager version 5.4 and Stata. Studies were included if they were RCTs involving anesthetized adult patients comparing esketamine with others, reporting of perioperative outcomes and sufficient data for meta-analysis. Studies were excluded for being reviews/editorials/case reports, conference abstracts, pediatric-focused, unpublished, or non-English. Primary outcomes contained change in anxiety/depression score and anxiety/depression Score. Secondary outcomes contained change in sleep/pain score and perioperation data. To assess publication bias, funnel plot visualization and Egger’s test were employed.ResultsA total of eight RCTs involving 1,101 participants fulfilled the inclusion criteria. The pooled analysis indicated that esketamine administration led to a significant reduction in perioperative anxiety levels compared to control interventions (SMD = −0.36; 95% CI: −0.67 to −0.06; p < 0.0001; I² = 84%). However, no statistically significant improvements were observed in sleep parameters, pain relief, surgical or anesthetic duration, or intraoperative metrics such as fluid administration, blood loss, urine output, or adverse event rates. Sensitivity analyses suggested variability in the anxiety-related outcomes, while findings related to depression remained consistent. Subgroup evaluations indicated a lack of measurable benefit in individuals under 40 years of age, those undergoing abdominal operations, and patients receiving spinal anesthesia.ConclusionEsketamine shows promise in reducing anxiety during the perioperative period. Nonetheless, its effectiveness may depend on individual patient profiles and surgical settings. Further high-quality trials are needed to identify the most effective dosing regimens, delivery methods, and combination strategies to enhance efficacy and reduce side effects.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO identifier CRD420251050362.